Comprehensive simulation study on CT isotope imaging beyond the experiment on the 208Pb based on nuclear resonance fluorescence. Issue 7 (3rd July 2022) - Negm, Hani; Zen, Heishun; Ohgaki, Hideaki
ABSTRACT: The isotope imaging technique based on Nuclear Resonance Fluorescence and Computed Tomography (NRF-CT) has been studied in experiments at the UVSOR-III facility besides comprehensive simulations. The laser Compton scattering γ-ray beam, whose maximum energy was 5.56 MeV, in UVSOR-III using the natural lead as a tested CT-target is utilized to demonstrate the efficacy of the NRF-CT technique. A 208 Pb has been selected as the isotope of interest with resonance energy at 5292 keV with J π = 1 – . To further understand the experimental results, Monte Carlo (MC) particle transport simulation, using GEANT4, was carried out. The NRF events distribution in the target, the witness-foils, and absorbers were investigated to optimize the experiment's geometry configuration for future investigations. The relative contribution of the NRF-events in the detection system from all experimental design materials has been estimated using MC simulation. A CT-isotope image (CTII) for 208 Pb has been reconstructed from the experimental results, and the simulation outcome validated. The spatial resolution of the reconstructed image is consistent with the measured object. Moreover, to improve the future experiment results, an additional simulation is developed in terms of the target configuration materials and the CT-target rotation matrix elements. Significant improvement in the CTII has been gained after assigning new parameters beyond the experiment configuration. Graphical abstract: uf0001